The life of Selina Campbell : a fellow soldier in the cause of restoration - Long, Loretta M. (Loretta Marie), 1971- (Tuscaloosa : University of Alabama Press, 2001)
This first biography of Selina Campbell opens a window onto the experience of women in one of the most dynamic religious groups of 19th-century America. Loretta M. Long examines the life and influence of Selina Campbell, one of the most visible women in the 19th-century Disciples of Christ movement. Best known as the wife of Alexander Campbell, founder of the Disciples, Selina Campbell both shaped and exemplified the roleof women in this dynamic religious group (also known as the Stone-Campbell movement). Her story demonstrates the importance of faith in the lives of many women during this era and adds a new dimension to the concept of the "separate spheres" of men and women, which women like Campbell interpreted in the context of their religious beliefs. A household manager, mother, writer, and friend, Campbell held sway primarily in the domestic sphere, but she was not held captive by it. Her relationship with her husband was founded on a deep sense of partnership conditioned by their strong faith in an all-powerful God. Eachof them took on complementary roles according to the perceived natural abilities of their genders: Alexander depended on Selina to manage his property and raise the children while he traveled the country preaching. Campbell outlived her husband by 30 years, and during that time published several newspaper articles and supported new causes, such as women in missions. In the end, as Long amply demonstrates, Selina Campbell was neither her husband's shadow nor solely a domestic worker. She was, in her husband's eyes, a full partner and a "fellow soldier" in the cause of Restoration.
1 Bakewell Family 25 -- 2 Making of a Partnership 44 -- 3 "An Abiding Interest and Love" 101 -- 4 "Usefulness in a Wilderness" 132.
Includes bibliographical references (pages 201-229) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Master record variable field(s) change: 050
Keywords: Campbell, Selina Huntington, -- 1803?-1897.; Campbell, Selina Huntington, -- 1803?-1897.; Christians (Disciples of Christ) -- West Virginia -- Biography; Women in Christianity -- United States -- History -- 19th century; BIOGRAPHY & AUTOBIOGRAPHY -- Religious; RELIGION -- Christianity -- Baptist; Christians (Disciples of Christ); Women in Christianity; United States; West Virginia; 1800-1899; Electronic books; Biography; History